Construction and Content Validation of an instrument for assessment holistic Knowledge Management (Perspectivas em Ciência da Informação, 2021)
Knowledge Management is a field of research that seeks to articulate the intricate relationship between the various organizational dimensions that influence in favor of knowledge. Measurement, as a dimension of this management, proposes to measure the level or capacity of knowledge management in organizational locus. However, the instruments for this purpose are expressed without an apparent psychometric assessment, as well as they do not articulate the holistic perspective, embodied by the totality of the critical dimensions for the success of this management. In the meantime, this research aims to build and validate an instrument for assessing holistic Knowledge Management. So, this is descriptive research with a quantitative approach, which makes use of the perception of four expert judges concerning the aspects of clarity, coherence, and pertinence of the statements of the constructed instrument. These aspects were analyzed using the Content Validation Coefficient method and must be equal to or greater than 0.70 to certify the quality of the questionnaire. The results express that the total coefficients, composed of all instrument items, are 0.87, 0.94, and 0.95 for each aspect, respectively, attesting to the quality of that instrument. Thus, this questionnaire can be applied for purposes of organizational diagnosis, which is an opportunity for future research.